Fabrication and Characterization of the Porous Ti4O7 Reactive Electrochemical Membrane - Qi, Guangfeng; Wang, Xiaohui; Zhao, Jingang; Song, Chunyan; Zhang, Yanbo; Ren, Feizhou; Zhang, Nan (Frontiers in Chemistry, 2022)
Preparation of the Magnéli Ti4O7 reactive electrochemical membrane (REM) with high purity is of great significance for its application in electrochemical advanced oxidation processes (EAOPs) for wastewater treatment. In this study, the Ti4O7 REM with high purity was synthesized by mechanical pressing of TiO2 powders followed by thermal reduction to Ti4O7 using the Ti powder as the reducing reagent, where the TiO2 monolith and Ti powder were separated from each other with the distance of about 5 cm in the vacuum furnace. When the temperature was elevated to 1333 K, the Magnéli phase Ti4O7 REM with the Ti4O7 content of 98.5% was obtained after thermal reduction for 4 h. Noticeably, the surface and interior of the obtained REM bulk sample has a homogeneous Ti4O7 content. Doping carbon black (0wt%-15wt%) could increase the porosity of the Ti4O7 REM (38–59%). Accordingly, the internal resistance of the electrode and electrolyte and the charge-transfer impedance increased slightly with the increasing carbon black content. The optimum electroactive surface area (1.1 m2) was obtained at a carbon black content of 5wt%, which increased by 1.3-fold in comparison with that without carbon black. The as-prepared Ti4O7 REMs show high oxygen evolution potential, approximately 2.7 V/SHE, indicating their appreciable electrocatalytic activity toward the production of •OH.